2011
DOI: 10.2174/092986711795496782
|View full text |Cite
|
Sign up to set email alerts
|

It is All About Proteases: From Drug Delivery to In Vivo Imaging and Photomedicine

Abstract: Clinical studies provide overwhelming evidence for the importance of proteolytic imbalance and the upregulation of diverse protease classes in diseases such as cancer and arthritis. While the complex nature of proteolytic networks has hampered the development of protease inhibitors for these indications, aberrant enzyme activity could be successfully exploited for the development of proteasesensitive drug delivery systems and fluorescent in vivo imaging agents. More recently, these concepts have also been tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 195 publications
0
19
0
Order By: Relevance
“…Recently, work has shown that certain extracellular proteases have anti-tumor properties 2. Yet, overexpressed proteases have been identified in cancerous cells numerous concentration folds higher than in healthy cells 16. Therefore the development of PAPs allows for specific, active drug delivery to cancer sites.…”
Section: Target Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, work has shown that certain extracellular proteases have anti-tumor properties 2. Yet, overexpressed proteases have been identified in cancerous cells numerous concentration folds higher than in healthy cells 16. Therefore the development of PAPs allows for specific, active drug delivery to cancer sites.…”
Section: Target Proteasesmentioning
confidence: 99%
“…Cathepsin-catalyzed substrate cleavage usually involves nucleophilic cysteine thiol, histidine, and an aspartate in the active site and cleavage is favored by acidic conditions 16. However, specific substrates of cysteine cathepsins involved in pathological conditions need to be determined 19.…”
Section: Target Proteasesmentioning
confidence: 99%
“…4b, 9 One characteristic that all these drug conjugates must share is the ability to effectively release their cargo in an active form at the target site. A popular method for this is the use of stimuli-sensitive linkers 10 between the drug and carrier that can selectively release the drug, examples of which include pH-, 11 reduction-, 2, 12 or enzyme-sensitive 13 linkers. The linker is thus of critical importance in determining the overall efficacy of the delivery system and, at times can be complicated by the auxiliary segment 5b, 14 and also by drug’s chemical structure.…”
mentioning
confidence: 99%
“…Thus, protease activity at the site of tissue disease can be capitalized upon to trigger and regulate the on-demand release of therapeutic agents from carrier vehicles. For example, systems that incorporate peptide sequences that are susceptible to cleavage by MMPs (Lutolf et al 2003b ;Harris et al 2008 ;Gabriel et al 2011 ), are widely used for GF delivery. More specifi cally, PEG- (Zisch et al 2003 ;Phelps et al 2010 ) and fi brin-based (Ehrbar et al 2007 ) hydrogels incorporating MMP-cleavable peptide sequences, in addition to presenting RGD-containing peptides for cell recruitment and/or adherence, have been shown to enable in situ release of immobilized VEGF, towards stimulating functional vascularization in animal models of hindlimb ischemia (Ehrbar et al 2007 ;Zisch et al 2003 ;Phelps et al 2010 ).…”
Section: Protease-triggered Gf Releasementioning
confidence: 99%